Land Use and Climate Change Impacts on the Reliability of Hydroelectric Energy Production - Baltas, E. A.; Karaliolidou, M. C. (Strategic Planning for Energy and the Environment, 2023)
This article examines the impacts of land use and climate change on the operational reliability of a multipurpose reservoir in Northern Greece. Four land use change scenarios (deforestation by 5%, 10%, and 20%, and reduction of agricultural land by 10%) and a climate change scenario (HadCM2) were examined. A reservoir simulation model was applied for the period 2008–2050, and the sensitivity of the risk associated with the annual hydroelectric energy production was evaluated under conditions of altered runoff. Significant increases of the risks associated with the annual energy production were observed, under both climate and land use change scenarios.